Termite Identification Attacks on Buildings - Niken Subekti; Anita Fadhila (Biosaintifika: Journal of Biology & Biology Education, 2023)
House construction continues from time to time, the frequency of termite attacks on buildings in the area is also very high due to the disturbance of the termite's natural habitat. Termites target the structural wood of buildings and objects derived from cellulose. This study aims to analyze the diversity of termite, house component damage, the relationship between the age and condition of building in Jakarta, Indonesia . This study used a purposive sampling method from 134 houses in Jakarta, Indonesia with a cross-sectional approach. The research procedures included taking and identifying specimens, analyze the intensity percentage of building damage, analyze the relationship between the age of the building and the condition of the building, and environmental factors. Based on the results of research conducted on 134 houses in Jakarta, it is concluded that there are four types of termites in the study sites: C. curvignathus (61.14%), M. gilvus (18.65%), M. inspiratus (10.88%), and C. cynocephaus (9.33%). The worst damage to residential components is found in the sills. Based on statistical tests, there is a correlation between age and the condition of the building. It indicates that the age of the building is significantly related to its condition.